Seasonal Variations in Seminal Characteristics of Patanwadi Ram - DABAS, S D; SUTHAR, B N; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
A total of 150 ejaculates were collected at weekly intervals during pre-breeding, breeding and post-breedng seasons from six native Patanwadi rams of 2-4 years of age to study the physical seminal characteristics. The mean values for different semen characteristics ’were : Volume of ejeculate 0.96±0.03" ml; pH 6.75±0.02; sperm concentration 2735.8±0.04 millions/ ml; dead sperm per cent 8.9±0.02 and abnormal sperm per cent 7.9±0.01. The colour and consistency in most of the samples was either creamy thick ( 48%) or creamy white thick ( 42.66%). The percentage of samples having mass activity+++, ++++ and +++++ were 36.66, 28.66 and 13.53 per cent, respectively. Season had a significant effect on mass activity, pH, sperm concentration, dead and abnormal sperm percentage.